Tinjauan Yuridis Sengketa Persamaan Merek Antara Starbucks Corporation Melawan PT Sumatra Tobacco Trading Company (Studi Putusan Pengadilan Negeri Niaga Nomor 51/Pdt.Sus/Merek/2021/PN Niaga JKT.PST. dan Putusan Mahkamah Agung Nomor 836K/Pdt.Sus-HKI/2022) - Berlianda Ester Septiani; Saidin; Aflah (Talenta Publisher, Universitas Sumatera Utara, 2023)
Brands provide a distinctive feature for goods or services of a company with goods or services of other similar companies, so brands are important for business people. The problems that will be discussed in this study are the protection of trademark rights holders according to Law Number 20 of 2016 concerning Trademarks and Geographical Indications, the process of resolving disputes over trademark equality in Indonesia, as well as legal analysis of trademark dispute decisions in the Commercial District Court Decision Number 51/Pdt.Sus/Merek/2021/PN Niaga Jkt. Pst. and Supreme Court Decision Number 836K/Pdt.Sus-HKI/2022. The research method used in this research is normative legal research. This research examines document studies, which uses various secondary data such as laws and regulations, court decisions, legal theories, and can be in the form of scholars' opinions. Trademark registration applied for by the owner of the Trademark if accepted will give rise to rights to the Trademark for the owner of the Trademark who registered the Trademark to the Directorate of Intellectual Property as a form of protection of trademark rights holders. If there is a trademark dispute, the settlement can be done by litigation and non-litigation. If the Trademark owner wants to do litigation, first the Trademark owner can file a lawsuit according to the procedures of the Trademark Act 2016. However, if you want to be resolved in non-litigation, it can be done through arbitration or alternative dispute resolution in accordance with Law Number 30 Year 1999 on Arbitration and Alternative Dispute Resolution.